On the Mechanism and Productivity of Single-Pulse Laser Fragmentation of Organic Curcumin Dispersions in a Continuous Flat Jet Flow-Through Reactor - Friedenauer, Tina; Spellauge, Maximilian; Sommereyns, Alexander; Rehbock, Christoph; Huber, Heinz Paul; Barcikowski, Stephan (Journal of Physical Chemistry C, 2025)
Curcumin is a natural food additive (nutraceutical), whose bioavailability is impaired by low solubility, a drawback which may be overcome by particle size reduction. Microparticle (MP) laser fragmentation in liquids (LFL) is an emerging production method for sensitive, organic submicron particles (SMPs) and nanoparticles (NPs), as it is characterized by processing at minimal chemical degradation. However, the fragmentation mechanisms need to be understood to tune the MP-LFL process toward a high SMP yield. Therefore, we used pump-probe microscopy (PPM) to elucidate the dynamics of shockwave formation and cavitation bubble growth on single-curcumin particles in correlation with laser fluence utilizing a ps-pulsed laser at 1040 nm. We observed LFL to occur at a threshold fluence of 60 mJ cm–2. Furthermore, we found a pressure buildup of 308 MPa within the particle, which exceeds the material’s tensile strength by one order of magnitude, hinting at strong contributions of photomechanical effects during curcumin MP-LFL. Consecutively, we examined the transfer to MP dispersions where concentration effects during MP-LFL were studied using a ps-pulsed laser at 532 nm and an optimized continuous flat jet (FJ) reactor, which is characterized by the ability to process particularly high concentrations of up to 1000 mg L–1 due to the low liquid layer thickness. An increased mass yield of SMP and NP (determined by UV–vis extinction spectroscopy and SEM) was found at high educt concentrations of 500 mg L–1, which leads to a relative SMP mass yield of 62% and a productivity of 278 mg h–1, with the potential for quantitative conversion of all MPs into SMPs at optimized illumination conditions (100% yield, 500 mg h–1). The outstandingly low by-product fraction (< 0.5%) by far surpasses the standard comminution processes applied today, rendering the MP-LFL technology even more relevant to the food or pharma secto
Keywords: Bubbles; Dietary supplements; Fragmentation; Lasers; Liquids